Application of RNA Interference Technology to Acroporid Juvenile Corals - Yuyama, Ikuko; Higuchi, Tomihiko; Hidaka, Michio (Frontiers in Marine Science, 2021)
Numerous genes involved in calcification, algal endosymbiosis, and the stress response have been identified in corals by large-scale gene expression analysis, but functional analysis of those genes is lacking. There are few experimental examples of gene expression manipulation in corals, such as gene knockdown by RNA interference (RNAi). The purpose of this study is to establish an RNAi method for coral juveniles. As a first trial, the genes encoding green fluorescent protein (GFP, an endogenous fluorophore expressed by corals) and thioredoxin (TRX, a stress response gene) were selected for knockdown. Synthesized double-stranded RNAs (dsRNAs) corresponding to GFP and TRX were transformed into planula larvae by lipofection method to attempt RNAi. Real-time PCR analysis to verify knockdown showed that GFP and TRX expression levels tended to decrease with each dsRNA treatment (not significant). In addition, stress exposure experiments following RNAi treatment revealed that planulae with TRX knockdown exhibited increased mortality at elevated temperatures. In GFP-knockdown corals, decreased GFP fluorescence was observed. However, the effect of GFP-knockdown was confirmed only in the coral at the initial stages of larval metamorphosis into polyps, but not in planulae and 1 month-old budding polyps. This study showed that lipofection RNAi can be applied to coral planulae and polyps after settlement, and that this method provides a useful tool to modify expression of genes involved in stress tolerance and fluorescence emission of the corals.